Defining constraints on the effects of framing on risky decisions - Bernardo, Allan B. I. (Philippine Journal of Psychology, 1992)
An experiment was conducted to study whether there are limits to the effects of framing on risk-taking decisions. The perceived weight of the decision (consequential or inconsequential), framing of the decision outcomes (positive or negative), and expected value of outcomes (low, moderate, or high) were manipulated to determine the effects on risk preference. The results show that with moderate expected values, the effects of framing were diminished if the decision problem was perceived to be consequential. With low and high Expected values, the effects of explicit framing are modified by the effects of the extreme expected values of the outcomes, the findings suggest that the mode in which people Perceive or frame decision outcomes are not rigid. When carefully scrutinizing outcomes, people may frame decision outcomes both positively and negatively. Extremely good or extremely bad outcomes might also weaken the tendency to perceive decisions in the corresponding opposite frame.